Post-COVID central hypersomnia, a treatable trait in long COVID: 4 case reports - Morelli-Zaher, Clémence; Vremaroiu-Coman, Andrea; Coquoz, Nicolas; Genecand, Léon; Altarelli, Marco; Binkova, Alzbeta; Frésard, Isabelle; Bridevaux, Pierre-Olivier; Gex, Grégoire (Frontiers in Neurology, 2024)
Introduction Fatigue is the most commonly reported post-COVID symptom. A minority of patients also report excessive daytime sleepiness, which could be a target for treatment. Methods Among 530 patients with a post-COVID condition, those with excessive daytime sleepiness were systematically assessed for objective central hypersomnia, with exclusion of all cases not clearly attributable to SARS-CoV-2 infection. Results Four cases of post-COVID central hypersomnia were identified, three fulfilling the criteria of the 3rd International Classification of Sleep Disorders for idiopathic hypersomnia, and one for type II narcolepsy. We report here their clinical history, sleep examination data and treatment, with a favorable response to methylphenidate in three cases and spontaneous resolution in one case. Conclusion We highlight the importance of identifying cases of post-COVID central hypersomnia, as it may be a treatable trait of a post-COVID condition.